Improving intrusion detection in SCADA systems using stacking ensemble of tree-based models - Duc-Duong Nguyen; Minh-Thuy Le; Thanh-Long Cung (Bulletin of Electrical Engineering and Informatics, 2022)
This paper introduces a stacking ensemble model, which combines three single models, to improve intrusion detection in supervisory control and data acquisition (SCADA) systems. The first layer of the proposed model is the combination of random forest, light boosting gradient machine, and eXtreme gradient boosting models. We use an multilayer perceptron (MLP) network as a meta-classifier of the model. The proposed model is optimized and tested on an international dataset (gas pipeline dataset). The tested results show an accuracy of 99.72% with the f1-score of 99.72% for binary classification tasks (attacked or non-attacked detection). For categorical tasks, the detection rates of almost all attack types are higher than 97.55% (except for denial of service (DoS)-95.17%), with an overall accuracy of 99.62%.